An Estimate of Protective Immunity against SARS-CoV2: Comparison of Different Vaccine Types - Waseem Iqbal; Ikram Ullah; Uroosa Irum; Saima Siddiqi; Khalid Mahmood Khan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Several types of vaccines have been approved to prevent SARS-CoV-2 infection. Few studies are conducted on the efficacy of COVID-19 vaccines. Vaccination is important to eliminate and fight SARS-CoV-2 infection and several vaccines have been approved. This study aimed to assess the incidence density of COVID-19 infection among the community, estimate the effectiveness of different types of vaccines (inactivated virus, viral vector or mRNA) and efficiency of incomplete and complete vaccination. In this observational cross-sectional study, a total of 4924 specimens were received from 1st January 2022 to 2nd February 2022 for the detection of SARS-CoV-2. The patient’s age, gender, and vaccination data were recorded and S, N, and ORF 1ab genes were amplified after RNA extraction through PCR. out of which 1034 (20.99%) cases were positive. Among 1034 (20.99%) positive cases, 418 and 616 patients were vaccinated and non-vaccinated respectively. The cases of SARS-CoV-2 in vaccinated patients were categorized into a sudden infection (≤ 10 days) and late infection (≥10 days) after the incomplete and complete dose of vaccination. Vaccination provides partial protection against SARS-CoV-2 infection. This might be due to the low efficacy and inability to detect recent variations in the protein structure of the virus.